A dual role for UCMA in osteoarthritis-Inhibition of aggrecanases and promotion of bone turnover - Stock, Michael; Menges, Stefanie; Eitzinger, Nicole; Gesslein, Maria; Botschner, Renate; Wormser, Laura; Distler, Alfiya; Schlötzer-Schrehardt, Ursula; Dietel, Katharina; Distler, Jörg; Beyer, Christian; Gelse, Kolja; et al. (Arthritis and Rheumatology, 2017)
Cartilage damage and subchondral bone changes are closely connected in osteoarthritis. How these processes are interlinked is however incompletely understood to date. Here, we investigate the mechanistic role of the cartilage-derived protein UCMA in osteoarthritis-related cartilage and bone changes.UCMA expression was assessed in healthy and osteoarthritic human and mouse cartilage. DMM-induced osteoarthritis was performed in WT and Ucma-deficient mice analysing cartilage and bone changes. UCMA-collagen interactions, effect of UCMA on aggrecanase activity and the impact of recombinant UCMA on osteoclast differentiation were studied in vitro.UCMA was found overexpressed in human and mouse osteoarthritic cartilage. DMM-triggered cartilage changes were aggravated in Ucma-deficient mice compared to WT littermates, showing increased structural damage, proteoglycan loss and chondrocyte cell death indicating chondroprotective effects of UCMA. Moreover, UCMA inhibited ADAMTS-dependent aggrecanase activity and directly interacted with cartilage-specific collagen types. In contrast, osteoarthritis-related bone changes were significantly reduced in Ucma-deficient mice, showing less pronounced osteophyte formation and subchondral bone sclerosis. Mechanistically, UCMA directly promoted osteoclast differentiation in vitro.UCMA links cartilage with bone changes in osteoarthritis, supporting cartilage integrity as an endogenous inhibitor of aggrecanases on the one hand, and promoting osteoclastogenesis and subchondral bone turnover on the other hand. Hence, UCMA represents an important link between cartilage and bone in osteoarthritis. This article is protected by copyright. All rights reserved.
EVALuna2:10230

Proteomic Analysis of a Fraction with Intact Eyespots of Chlamydomonas reinhardtii and Assignment of Protein Methylation - Eitzinger, Nicole; Wagner, Volker; Weisheit, Wolfram; Geimer, Stefan; Boness, David; Kreimer, Georg; Mittag, Maria (Frontiers in Plant Science, 2015)
Flagellate green algae possess a visual system, the eyespot. In Chlamydomonas reinhardtii it is situated at the edge of the chloroplast and consists of two carotenoid rich lipid globule layers subtended by thylakoid membranes (TM) that are attached to both chloroplast envelope membranes and a specialized area of the plasma membrane (PM). A former analysis of an eyespot fraction identified 203 proteins. To increase the understanding of eyespot related processes, knowledge of the protein composition of the membranes in its close vicinity is desirable. Here, we present a purification procedure that allows isolation of intact eyespots. This gain in intactness goes, however, hand in hand with an increase of contaminants from other organelles. Proteomic analysis identified 742 proteins. Novel candidates include proteins for eyespot development, retina-related proteins, ion pumps, and membrane-associated proteins, calcium sensing proteins as well as kinases, phosphatases and 14-3-3 proteins. Methylation of proteins at Arg or Lys is known as an important posttranslational modification involved in, e.g., signal transduction. Here, we identify several proteins from eyespot fractions that are methylated at Arg and/or Lys. Among them is the eyespot specific SOUL3 protein that influences the size and position of the eyespot and EYE2, a protein important for its development.
Keywords: ATP synthase; Chlamydomonas reinhardtii; EYE2; eyespot proteome; phototaxis; protein methylation; SOUL hems-binding protein 3